Biomimetic photonic coatings using squid reflectin protein - Loke, Jun Jie (Nanyang Technological University, 2022)
Squids are masters of camouflage in the Animal Kingdom. They use metachrosis to dynamically control the morphology of dermal cells – chromatophore and iridophore – that regulate body colouration and patterns to convey signals. This is prevalent in Nature and typically serves important survival functions to deter predators, capture prey or for mating strategies Squids in the Loliginidae family (which included Sepioteuthis lessioniana used in this study) possess the unique capability to dynamically modulate the iridescent properties of their skin by tuning and controlling the internal assembly and periodicity of Bragg-like reflector platelets located within iridophores, which are entirely made of proteins called reflectins. These iridescent light reflective-refractive structures rely on Bragg reflectors, making use of periodic spacing of photonic crystals and thin film constructive interference. Previous studies have demonstrated that these photonic changes are regulated by phosphorylation/dephosphorylation of condensed reflectin nanoparticles in the reflector platelets. Since the size of the reflectin nanoparticles affect the iridescence properties, it was hypothesized that the colour of films/coatings made of reflectin nanoparticles could be regulated by changing the size of reflectin nanoparticles that they are made of. Thus, the main goal was to self-assemble reflectin nanoparticles with well-controlled particle size and investigate if Sepioteuthis lessioniana reflectin B1 (SlRF-B1) nanoparticle was able to self-assemble into photonic lattices to produce structural colouration or iridescence. This thesis describes a systematic approach to self-assemble SlRF-B1 into discrete nanoparticle sizes when conjugated with click-chemistry ligand dibenzocyclooctyne (DBCO)-sulfo-NHS ester. This was achieved by varying the solvent conditions during the self-assembly process. These quasi-monodisperse nanoparticles were subsequently immobilised onto azide-functionalised wafer surface using click-chemistry, resulting in monolayer assemblies where its photonic properties were investigated. These DBCO-SlRF-B1 nanoparticles produced reflectance in the visible wavelength when inter-particle spacing was less than 1 μm. The monolayers exhibit a tunable reflectance response from violet (400 nm) to infrared-red (800 nm).